Integration of Nutrient Sensing in Fish Hypothalamus - Soengas, José L. (Frontiers in Neuroscience, 2021)
The knowledge regarding hypothalamic integration of metabolic and endocrine signaling resulting in regulation of food intake is scarce in fish. Available studies pointed to a network in which the activation of the nutrient (glucose, fatty acid, amino acid) sensing systems would result in AMPK inhibition and activation of Akt and mTOR. Changes in these signalling pathways would control phosphorylation of transcription factors CREB, FoxO1, and BSX leading to food intake inhibition through changes in the expression of neuropeptides NPY, AgRP, POMC, and CART. The present mini-review summarises information on the topic and identify gaps for future research